B-cell epitope prediction of MPB83 protein as a candidate for serodiagnostic antigen of bovine tuberculosis in human: In silico study - Ahmad, Shabrina Izzata Afiyati; Aziz , Ayu Munawaroh; Armiyanti, Yunita; Mufida, Diana Chusna (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Background: Bovine tuberculosis (bTB) can be transmitted to humans by inhalation or consumption of incomplete pasteurized milk and dairy products derived from infected cows. Most cases of Mycobacterium tuberculosis (M. bovis) infection are resistant to tuberculosis (TB) drugs. The risk of death during treatment for bTB has been reported to be 2.55 times higher than for TB. However, the quality of diagnostic methods for bTB remains relatively low.Objective: We aim to evaluate the potential of the B-cell epitope of the MPB83 protein as a candidate bTB serodiagnostic antigen using an in silico approach. Methods: This study was a computer-based descriptive study using secondary data from the National Center for Biotechnology Information (NCBI) protein database. The MPB83 protein sequence was obtained from M. tuberculosis variant bovis AF2122/97 from the United Kingdom. We described the characteristics of the linear epitope of the M. bovis B-cell protein MPB83 by measuring antigenicity, molecular weight, instability index, and Grand Average of Hydropathy (GRAVY) score. The tools used in this study were IBIVU PRALINE, VaxiJen v2.0, IEDB, ExPASy ProtParam, Cluspro, and the PyMOL application.Results: We found an epitope that could be used for bTB serodiagnostic antigen with low conservation, the 106KLNPDVNLVDTLN118 epitope. It has the molecular weight, instability index, and GRAVY score of 1638.76 Da, -28.44, and -0.300, respectively. Epitopes with the best criteria were simulated by docking to human major histocompatibility complex (MHC) class II. Docking results showed that the lowest binding energy was -644.8 kcal/mol. Further analysis using the PyMOL application obtained 14 hydrogen bonds with bond distances ranging from 1.7 Å to 2.2 Å, all of which showed strong hydrogen bonds.Conclusion: The B-cell epitope of MPB83 protein sequence 106KLNPDVNLVDTLN118 has a potential serodiagnostic antigen candidate for human bTB.